Preparation of paddy straw based complete feed pellets and their impact on the performance of buffalo calves - WADHWA, M; HUNDAL, J S; BAKSHI, M P S (The Indian Journal of Animal Sciences, 2021)
This study was planned to prepare paddy straw based complete feed pellets and to assess their impact on the performance of buffalo calves. Iso-nitrogenous and isocaloric complete feed pellets containing 25, 35 and 45% paddy straw, alfalfa hay and concentrate mixtures were prepared. The roughage to concentrate ratio in the pellets was maintained at 65:35. The CP, EE and cell wall contents in all pellets were comparable. The bulk density of complete feed pellets increased (p<0.05) with the increase in paddy straw level. The in vitro studies revealed that NGP, true OM digestibility and ME content decreased linearly with the increase in paddy straw level from 25 to 45% in the pellets. The 104 days growth trial on buffalo calves revealed that the daily DM intake, digestibility of most of nutrients and N-retention decreased (P<0.05) linearly with the increase in level of paddy straw in buffalo calves fed complete feed pellets. The rumen studies revealed that total VFAs, acetate, propionate and isovalerate production; and microbial biomass synthesis was the highest in calves fed pellets containing 35% paddy straw, statistically comparable with those fed pellets containing 25% paddy straw. But these parameters were depressed (P<0.05) in animals fed pellets containing 45% paddy straw. It can be concluded that isonitrogenous and iso-caloric complete feed pellets containing paddy straw up to 35% can be utilized effectively without affecting the health and performance of buffalo calves.